Nitrogenated Fertilization In Pasture Brachiaria Brizantha Cv. Marandu Via Organic Compounds - G. R. Soares; V. B. Tavares; A. P. Neiva Júnior; L. O. Fernandes (Boletim de Indústria Animal)
The objective was to evaluate the quantitative and qualitative effect of fertilization of Brachiaria brizantha cv. Marandu using nitrogen from liquid cattle manure and organomineral fertilizer. The experiment was developed in a pasture already established and soil analysis of this area was made for the necessary corrections. The experimental design was randomized blocks in a 4 x 2 factorial scheme. The treatments consisted of control with 0 kg/ha of N, 3 treatments with application of bovine liquid manure and 3 treatments with organomineral fertilizer in the dosages of 60, 120 and 180 kg/ha of N. Three cuts were made in Marandu grass when the pasture reached 30 cm in height, leaving a residue of 15 cm, the production of DM, leaf production, stem, CP, NDF and ADF were evaluated. At the end of the experiment, the cost of fertilizing with manure and organomineral fertilizer was done. To compare the averages obtained and the morphological components of each sample, the Tukey test at 5% significance was used, with the aid of the SISVAR statistical program. With the highest nitrogen levels of organomineral fertilizer and the bovine liquid manure, a higher CP content was obtained, reaching 9.30; 7.78 and 7.90% in the first cut, with organo 180, 120 and manure 180 respectively. Fertilizations with manure 60 and 180, organomineral 120 and 180 showed the lowest values for NDF in the first cut, the ADF only showed a significant difference in the second cut with organo 60, manure 120 and 60 with the highest values. Organomineral fertilizer in different doses provided higher production, but at a higher cost. Fertilization improved the quality of the forage.